Pharmacokinetics of Iodine and Fluoride following Application of an Anticaries Varnish in Adults. (July 2018) - Lin, Y.S.; Rothen, M.L.; Milgrom, P.
Researchers have suggested that combining topical fluoride with an antiseptic to reduce cariogenic bacteria may be more effective than fluoride application alone in preventing dental caries. In previous studies, povidone iodine (PVP-I), a widely used bactericidal antiseptic, and sodium fluoride (NaF), used to foster remineralization of enamel, were applied sequentially topically and shown to be safe and effective. The study aim was to characterize the kinetics of iodine and fluoride following topical application of a single combination PVP-I and NaF anticaries varnish in healthy adults. Sixteen participants (aged 23 to 57 y) participated in a pharmacokinetics study following the application of 0.4 mL varnish containing 10% (w/v) PVP-I and 5% (w/v) NaF. Serum and urine samples were collected at various time points over 24 h following application of varnish. Iodine and fluoride concentrations were analyzed, and for each time point, baseline concentrations were subtracted from observed values. Following varnish application, 2 of 16 participants had nearly undetectable baseline-corrected iodine and fluoride levels, suggesting minimal absorption, lack of release of iodine and fluoride from the varnish, or inconsistent dosing. The average peak concentrations were 57 ± 33 ng/mL iodine and 60 ± 34 ng/mL (0.060 ± 0.034 ppm) fluoride and occurred within 3 h of application. The average elimination half-life was 5.5 ± 1.4 h and 3.1 ± 1.6 h for iodine and fluoride, respectively. Renal clearance of iodine and fluoride was similar to literature values. No adverse events related to the study varnish were observed by the investigative team or reported by the participants. In this study, serum fluoride and iodine transiently increased but were within normal range 24 h after application of the varnish. This study has shown that the combination of PVP-I and NaF in a proposed anticaries varnish was well tolerated. Knowledge Transfer Statement: This clinical study demonstrated that a dental varnish combining 10% (w/v) povidone iodine and 5% (w/v) sodium fluoride is well tolerated. Serum fluoride and iodine transiently increased but were within normal range after 24 h. Further studies should be conducted to assess the efficacy of a combination in preventing dental caries, especially in high-risk populations.